2000
DOI: 10.1542/peds.106.6.1374
|View full text |Cite
|
Sign up to set email alerts
|

Teething and Tooth Eruption in Infants: A Cohort Study

Abstract: This study did not confirm the expected strong associations between tooth eruption and a range of teething symptoms in children 6 to 30 months old, although we cannot rule out the possibility that weak associations may exist (Type II error). These findings contrast with strong parent and professional beliefs to the contrary. Such beliefs may preclude optimal management of common patterns of illness and behavior in young children.teething, infants, symptoms, tooth eruption, illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
101
0
24

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(133 citation statements)
references
References 15 publications
8
101
0
24
Order By: Relevance
“…However, the study conducted in Australia found no associations between teething in institutionalized infants and signs and symptoms. 11 The conclusion of all prospective studies is that no specific symptoms can reliably predict the emergence of a tooth. Furthermore, signs and symptoms that can be attributed to teething are not serious; thus, the presence of fever (Ͼ38.5°C) or other clinically important symptoms is very unlikely to be caused by tooth eruption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the study conducted in Australia found no associations between teething in institutionalized infants and signs and symptoms. 11 The conclusion of all prospective studies is that no specific symptoms can reliably predict the emergence of a tooth. Furthermore, signs and symptoms that can be attributed to teething are not serious; thus, the presence of fever (Ͼ38.5°C) or other clinically important symptoms is very unlikely to be caused by tooth eruption.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although some studies involving parents, pediatricians, and other health care professionals have associated teething with signs and symptoms, [2][3][4][5][6][7][8][9] prospective studies have offered contradictory findings. 10,11 In a study involving 21 children aged between 6 months and 2 years institutionalized at day care centers in Melbourne, Australia, tympanic temperature readings and clinical oral examinations were conducted, and the results did not confirm any association between tooth eruption and disturbances. 11 However, such an association was found in a study conducted in Cleveland, Ohio, involving 111 infants between 3 and 5.6 months of age at the beginning of the data-collection period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have failed to identify daytime restlessness, diarrhoea, bronchitis, an increase in finger sucking, gum rubbing, drooling and a loss of appetite in teething children, 9,13 whilst Wake et al (2000) 11 could not confirm a strong association between a range of teething symptoms and tooth eruption. Although Macknin et al (2000) 1 identified several symptoms (see above) to be associated with teething, congestion, sleep disturbance, stool looseness, increased stool number, decreased liquid appetite, cough, non-facial rashes, fever and vomiting were not significantly associated with tooth emergence.…”
Section: Symptomsmentioning
confidence: 96%
“…However, some studies found no associations with teeth eruption and health problems such as infections, fever, and diarrhea. [19,20] In this study, 1.3% mothers had taken no action in response to the health problems of children. One fourth of mothers had treated their children at home; majority of them bought medicines from prescriptions or experience of previous illness followed by home remedies.…”
Section: Discussionmentioning
confidence: 67%